A Need Analysis of English Course for Agriculture Department Students - Alfi Hidayatu Miqawati; Ikrima Halimatus Sa’diyah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The process of doing a needs analysis becomes essential since it gives instructional designers the chance to create learning materials that will actually benefit the target audiences. The present study aimed at scrutinizing the students’ needs to develop an English course for agriculture students in Indonesian vocational higher education or polytechnic. The researchers try to bring novelty in the present study by considering CEFR framework as a standard for describing and determining the level of ability or proficiency. Convergent parallel mixed methods design was employed in the current study. The data were obtained from questionnaires, interviews and focused group discussion. The questionnaire was distributed to the agriculture department students, employing a stratified random sampling method. In addition, the interview and focused group discussion were done with the coordinators of study program, the Head of Quality Assurance, lecturers who taught Intermediate English Course, and industry partners as well. The data collected from questionnaires, interview, and focused group discussion were then analyzed using side-by-side comparison. The results disclosed that the language skill considered the most important for the agriculture department students is speaking skill since it has a great impact on students’ academic, social and professional development. In other words, the agriculture department students require a learning process that emphasizes practice over theory. Furthermore, to make classroom activities more exciting, they desire the learning process that is blended with games. As a result, this study also provides implications for course designers to develop English materials that reflect comprehensive needs of the students.